SCREENING PHYTOCHEMICALS AND ANTIBACTERIAL ACTIVITY OF MICROALGAE STRAIN Scenedesmus sp. AUMA-020 - Neri Fadjria; Arfiandi Arfiandi; Dewi Nofita; Mazaya Fadhila (Journal of Pharmaceutical and Sciences, 2023)
In this study was aimed at identifying active substances that can be used as antibacterial agents. To reach this target, different solvent extracts (n-hexane and methanol) of microalgae strain Scenedesmus sp. AUMA-020 were examined. Phytochemical screening of n-hexane extract from microalgae strain Scenedesmus sp. AUMA-020 showed the presence of terpenoids and saponins, while methanol extracts contained flavonoids, phenolics, steroids, terpenoins and saponins. N-hexane extract has strong antibacterial activity compared to methanol extract. Both extracts isolates showed no antibacterial activity against Escherichia coli bacteria. In conclusion, the studied microalgae strain Scenedesmus sp. AUMA-020 can be considered as a potential natural source of bioactive compounds with antibacterial activity.